Effect of an integrated maternal health intervention on skilled provider’s care for maternal health in remote rural areas of Bangladesh: a pre and post study - Huq, Nafisa Lira (BMC Pregnancy Childbirth, 2015)
BACKGROUND: An integrated maternal health intervention in a rural sub district of Bangladesh focused on the training and deployment of a required number of Community Based Skilled Birth Attendants (CSBAs). The aim of the study was to assess the effect of the intervention on use of skilled provider care during pregnancy, delivery and after delivery. METHODS: The effect compared the skilled providers care in low performing areas with high and medium performing areas through pre–and post–intervention surveys. The post-intervention survey was conducted two years after the completion of the intervention. Village clusters, with populations of approximately 3000, were randomly assigned to the surveys. Mothers who had delivered within the 6 months prior to the surveys, were recruited for the structured interviews. Logistic regression was conducted to compare the effect. RESULTS: Majority of mothers in the low performing areas belonged to a poor economic quintile. The level of skilled attendance for 4+ Antenatal Care (ANC) and delivery increased sharply from baseline to endline survey in low performing areas (ANC: 1.6% to 15.3%, p < 0.0001; skilled birth attendant at delivery: 12.6% to 38.3%, p < 0.0001). Less than 1% of the women received Post Natal Care (PNC) from a skilled provider prior to the intervention, and this proportion increased to 20% at the end of the intervention. Adjusted odds showed that the intervention had an effect on the individual performing area on use of skilled provider care during ANC, delivery and PNC. The increase of 4+ ANC from skilled providers and skilled birth attendants during delivery in the low performing areas due to the integrated maternal health intervention was significant relative to the increase in the high performing areas [4+ ANC from skilled providers – OR: 3.8 (1.9–7.6); skilled birth attendants – OR: 2.8 (2.1–3.8)]. CONCLUSION: An integrated maternal health care intervention focused on deployment of a required number of CSBAs increased the opportunity for underprivileged women to benefit from skilled providers care during their pregnancy. This integrated intervention might improve the maternal health in developing countries where home delivery with unskilled attendants is common.